After innovation: protecting intellectual property during production – Canica Design Inc - Ensign, Prescott C.; Lanney, Andrew (Université d'Ottawa | University of Ottawa, 2008)
This case study examines the challenges of a small product design company to bring innovative surgical instruments and wound closure devices to domestic and international medical markets quickly and efficiently, while still protecting intellectual property.